Decomposition of Polish International Investment Position with Selected Countries of Central and Eastern Europe - Maciejczyk-Bujnowicz, Iwona (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
At the turn of the twentieth and twenty-first century, worldwide significant changes were made in the structure of the external investment position. In Asia and in the countries of the Middle East, there was recorded a dynamic growth of financial surpluses, while in other developing countries there was noted a significant increase of the equity in liabilities and a strong accumulation of foreign exchange reserves. Generally, in the era of financial globalization since the 70s and 80s followed by a dynamic increase in the share of IIP liabilities in the GDP of developed countries. From the 90s to the beginning of the XXI century, we can note a high growth rate of the share of equity capital in the capital structure. The aim of the study is to analyze the international investment position of Poland to selected countries of Central and Eastern Europe and the countries in the euro area.